2015
DOI: 10.1007/s11999-015-4281-2
|View full text |Cite
|
Sign up to set email alerts
|

Blast Injury in the Spine: Dynamic Response Index Is Not an Appropriate Model for Predicting Injury

Abstract: BackgroundImprovised explosive devices are a common feature of recent asymmetric conflicts and there is a persistent landmine threat to military and humanitarian personnel. Assessment of injury risk to the spine in vehicles subjected to explosions was conducted using a standardized model, the Dynamic Response Index (DRI). However, the DRI was intended for evaluating aircraft ejection seats and has not been validated in blast conditions.Questions/purposesWe asked whether the injury patterns seen in blast are si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…However, lower spine injuries account for only 1% of spinal injuries in civilians . Other studies supported this by demonstrating 53% of 266 spinal fractures attributed to underbody blast affected T12‐L5 levels . Caudal injury migration may be attributable to severe loading conditions in military personnel during aircraft ejections, helicopter crashes, or underbody blasts .…”
mentioning
confidence: 99%
“…However, lower spine injuries account for only 1% of spinal injuries in civilians . Other studies supported this by demonstrating 53% of 266 spinal fractures attributed to underbody blast affected T12‐L5 levels . Caudal injury migration may be attributable to severe loading conditions in military personnel during aircraft ejections, helicopter crashes, or underbody blasts .…”
mentioning
confidence: 99%
“…It has also been observed that the injuries are predominantly distributed in the thoracolumbar spine. 1,14 It was also pointed out in Stemper et al 6 the importance of the inclusion of spine geometry and consideration of the eccentric loading on the spine to assess the occurrence of burst and wedge fractures of the vertebral segments. Thus, an injury parameter relating the compressions of all springs in between T1 and L5 were taken into account, and their sum was proposed as the injury parameter.…”
Section: Injury Parametermentioning
confidence: 97%
“…These are mainly caused due to high rate axial loading resulting in compression of vertebral height and increase in angulations of each vertebrae. Spurrier et al reported that wedge compression and burst fractures were most common in the blast loading scenarios and ejection injuries. It has also been observed that the injuries are predominantly distributed in the thoracolumbar spine .…”
Section: Mathematical Modellingmentioning
confidence: 99%
See 2 more Smart Citations